Evaluation of Cyclin D1 Expression in Aggressive and Nonaggressive Central Giant Cell Granuloma of the Jaws - Saede Atarbashi Moghadam; Maedeh Ghorbanpour (Shiraz University of Medical Sciences, 2018)
Statement of the Problem: Central giant cell granuloma of the jaws is comprised of two types namely aggressive and nonaggressive. Controversy exists regarding the histogenesis of this lesion. Up to now, there are no reliable histologic or molecular methods to differentiate aggressive from nonaggressive central giant cell granuloma of the jaw. Moreover, because of different treatment of two groups, correct diagnosis is needed. Purpose: The purpose of this study was to evaluate and compare the expression of cyclin D1 between aggressive and nonaggressive central giant cell granulomas of the jaws. Materials and Method: This retrospective study was performed on 16 paraffin blocks of aggressive central giant cell granuloma, and 16 nonaggressive central giant cell granulomas from Shahid Beheshti Oral Pathology Department and evaluated the expression of cyclin D1 on giant cells and mononuclear cells of the lesions. T-test was used for quantitative evaluation and comparison of cyclin D1 expression between two groups. Results: Overexpression of cyclin D1 in giant cells and mononuclear cells of the lesions of both groups was apparent, but no significant statistical difference was seen. Cyclin D1 positivity was seen predominantly in the nuclei of giant cells. When a giant cell was positive, all the nuclei showed immunoreactivity. In each group mean percentage of the positive giant cells were higher than positive mononuclear cells and significant statistical difference (p= 0.000) was seen between them. Conclusion: Probably overexpression of cyclin D1 implicates in the pathogenesis of the central giant cell granulomas but it seems that this protein could not be used as a marker for identifying the clinical behavior of these lesions. The term giant cell lesion (GCL) describes a group of intraosseous nonodontogenic benign lesions containing